Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.15408/inprime.v2i2.14482
|View full text |Cite
|
Sign up to set email alerts
|

Some Notes on Relative Commutators

Abstract: Let G be a group and α ϵ Aut(G).  An α-commutator of elements x, y ϵ G is defined as [x, y]α = x-1y-1xyα. In 2015, Barzegar et al. introduced an α-commutator of elements of G and defined a new generalization of nilpotent groups by using the definition of α-commutators which is called an α-nilpotent group. They also introduced an α-commutator subgroup of G, denoted by Dα(G) which is a subgroup generated by all α-commutators. In 2016, an α-perfect group, a group that is equal to its α-commutator subgroup, was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…Further results and wider study based on the 𝛼-normal subgroup can be found in Read (1976), Mazur (1994), Barzegar (2015), Kumar (2019), Ganjali & Erfanian (2020), Haghparast et. al., (2021), Haghparast et.…”
Section: Introductionmentioning
confidence: 91%
“…Further results and wider study based on the 𝛼-normal subgroup can be found in Read (1976), Mazur (1994), Barzegar (2015), Kumar (2019), Ganjali & Erfanian (2020), Haghparast et. al., (2021), Haghparast et.…”
Section: Introductionmentioning
confidence: 91%